Big Data and Individual Privacy in the Age of the Internet of Things - Mackenzie Adams (Technology Innovation Management Review, 2017)
The availability of “big data” and “smart” products are credited with advancing solutions to complex problems in medicine, transportation, and education, among others. However, with big data comes big responsibility. The collection, storage, sharing, and analysis of data are far outpacing individual privacy protections, whether technological or legislative. The Internet of Things (IoT), with its promise to create networks of networks, will magnify individual data privacy threats. Recent data breaches, exposing the personal information of millions of users, provide insight into the vulnerability of personal data. Although seemingly expansive, there are core individual privacy issues that are central to current big data breaches and anticipated IoT threats. This article examines both big data and the IoT using examples of data privacy breaches to illustrate the impact of individual data loss. Furthermore, the article examines the complexity of tackling technological and legislative challenges in protecting individual privacy. It concludes by summarizing these issues in terms of the future implications of the IoT and the loss of privacy.
Keywords: big data; cybersecurity; data breaches; Internet of Things; IOT; privacy; smart devices

Cybersecurity Skills Training: An Attacker-Centric Gamified Approach - Mackenzie Adams; Maged Makramalla (Technology Innovation Management Review, 2015)
Although cybersecurity awareness training for employees is important, it does not provide the necessary skills training required to better protect businesses against cyber-attacks. Businesses need to invest in building cybersecurity skills across all levels of the workforce and leadership. This investment can reduce the financial burden on businesses from cyber-attacks and help maintain consumer confidence in their brands. In this article, we discuss the use of gamification methods that enable all employees and organizational leaders to play the roles of various types of attackers in an effort to reduce the number of successful attacks due to human vulnerability exploits. We combine two separate streams – gamification and entrepreneurial perspectives – for the purpose of building cybersecurity skills while emphasizing a third stream – attacker types (i.e., their resources, knowledge/skills, and motivation) – to create training scenarios. We also define the roles of attackers using various theoretical entrepreneurial perspectives. This article will be of interest to leaders who need to build cybersecurity skills into their workforce cost-effectively; researchers who wish to advance the principles and practices of gamification solutions; and suppliers of solutions to companies that wish to build cybersecurity skills in the workforce and leadership.
Keywords: cyber attackers; cybersecurity; entrepreneur; gamification; training

Down the Rabbit Hole: How Structural Holes in Entrepreneurs' Social Networks Impact Early Venture Growth - Mackenzie Adams; Maged Makramalla; Walter Miron (Technology Innovation Management Review, 2014)
Social networks play a significant role in the success of new entrepreneurial ventures. They provide an accumulation of tangible and intangible resources that are linked to entrepreneurial outcomes such as growth and innovation. The structure of social networks, specifically, has been linked to these outcomes; structural holes in social networks have shown an association with entrepreneurial success. Entrepreneurs who have many structural holes in their networks are thought to benefit from a rich source of divergent information. This article examines the complex nature of the relationships among social networks, formal institutions, and the outcomes of new ventures. It also explores the effects of a social network’s structural holes on growth in the early years of a venture’s development. We propose that structural holes of a social network, through a mediating role of institutional polycentrism, play an important role in the growth and profitability of a new venture as well as potential threats of exploitation. We then provide recommendations based on the reviewed literature for entrepreneurs and managers of formal institutions.
Keywords: entrepreneurs; institutional order; social networks; structural holes; venture growth